2021
DOI: 10.14814/phy2.15084
|View full text |Cite
|
Sign up to set email alerts
|

Increased and continuous coronary arterial flow was induced by LV uncoupling condition using combined treatment of a microaxial heart pump and venoarterial extracorporeal membrane oxygenation

Abstract: An emerging therapeutic modality, ECPELLA, which combines a transvalvular microaxial left ventricular (LV) assist device, Impella, and venoarterial membrane oxygenation (VA‐ECMO), has been applied for patients with refractory cardiogenic shock. During ECPELLA support, VA‐ECMO increases the LV load, whereas the Impella reduces the LV load. Studies reported that coronary perfusion is influenced by LV unloading conditions, and the effective degree of LV unloading to increase the coronary perfusion on ECPELLA supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We have previously reported a case of increased coronary arterial flow by LV uncoupling (total LV support) by ECPELLA in which reduced arterial pulse pressure appeared to be associated with total LV support. 23 These results imply that superior clinical outcomes might be associated with both right (lower PAPI and CVP) and left ventricular unloading effects to reduce myocardial damage with higher total MCS flow compared to VA-ECMO. Saku at el.…”
Section: Discussionmentioning
confidence: 87%
“…We have previously reported a case of increased coronary arterial flow by LV uncoupling (total LV support) by ECPELLA in which reduced arterial pulse pressure appeared to be associated with total LV support. 23 These results imply that superior clinical outcomes might be associated with both right (lower PAPI and CVP) and left ventricular unloading effects to reduce myocardial damage with higher total MCS flow compared to VA-ECMO. Saku at el.…”
Section: Discussionmentioning
confidence: 87%
“…The Impella device is a percutaneous micro-axial continuous-flow pump that is used for patients with cardiogenic shock and left ventricular (LV) unloading [ 1 ]. Impella-assisted forward blood flow may increase coronary blood flow; however, only a few studies have investigated in vivo coronary flow with Impella support [ 2 ]. We present a case involving a patient with myocardial infarction and subsequent cardiogenic shock whose coronary blood flow in the left anterior descending artery (LAD), according to the support setting, was evaluated using transthoracic Doppler echocardiography during Impella weaning.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Additionally, we have recently reported a case where coronary flow was influenced by the degree of LV unloading on ECPELLA support. 5) Thus, it is essential to assess the degree of LV unloading for subsequent LV recovery with ECPELLA support. A previous study in a canine model revealed that the LV pressure (LVP) indicated the degrees of LV unloading on Impella support.…”
mentioning
confidence: 99%